Structural Validity Evidence for the Oxford Utilitarianism Scale Across 15 Languages - ÖZDOĞRU, ASİL (My University, 2024)
Abstract: Background: The Psychological Science Accelerator (PSA) recently completed a large-scale moral psychology study using translated versions of the Oxford Utilitarianism Scale (OUS). However, the translated versions have no validity evidence. Objective: The study investigated the structural validity evidence of the OUS across 15 translated versions and produced version-specific validity reports. Methods: We analyzed OUS data from the PSA, which was collected internationally on a centralized online questionnaire. We also collected qualitative feedback from experts for each translated version. Results: For each version, we produced version-specific psychometric reports which include the following: (1) descriptive item and demographics analyses, (2) factor structure evidence using confirmatory factor analyses, (3) measurement invariance testing across languages using multiple-group confirmatory factor analyses and alignment optimization, and (4) reliability analyses using coefficients α and ω. Keywords: Oxford Utilitarianism Scale, translation, measurement invariance, reliability, Psychological Science Accelerator
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Social Sciences and Humanities; Psychology; Temel Bilimler (SCI); PSİKOLOJİ, UYGULAMALI; Natural Sciences (SCI); PSYCHOLOGY; PSYCHOLOGY, APPLIED; Psikoloji (çeşitli); Sosyal Bilimler ve Beşeri Bilimler; Uygulamalı Psikoloji; Psychology (miscellaneous); Social Sciences & Humanities; Applied Psychology; measurement invariance; Oxford Utilitarianism Scale; Psychological Science Accelerator; reliability; translation; Oxford Utilitarianism Scale; translation; measurement invariance; reliability; Psychological Science Accelerator